PERLINDUNGAN HUKUM TERHADAP KONSUMEN PENGGUNA JASA TRANSPORTASI ONLINE - Anggun Lupita; M. Yasin Ardhy; Muhammad Fahruddin (Jurnal Hukum Jurisdictie, 2019)
Anggun Lupita, 2018, Legal Protection against Users of Online Transportation Services, Thesis, Faculty of Law, Islamic University as-Shafi'iyah, Jakarta. This research aims to find out the implementation of legal protections for consumers of online transportation service users who experience losses or accidents and dispute resolution of users of online transportation services. The purpose of this study is to find out how to implement legal protections for consumers of online transportation service users who experience losses or accidents. Formulation of the problem: (1) How to implement legal protections against consumers of online transportation service users. (2) How to resolve disputes with users of online transportation services. Company PT. Go-Jek as an online transportation provider company must provide compensation or insurance to consumers of online transportation service users in the form of Go-Car who have an accident, stipulated in Article 237 of Law No. 22 of 2009 on Traffic and Road Transportation expressly requires public transportation companies to follow the accident insurance program as a form of responsibility for insurance guarantees for accident victims. In the implementation of legal protections for consumers of online transportation service users who have a Go-Car accident, PT. Go-Jek as a transportation provider of Go-Jek only provides compensation or insurance of Rp 10,000,000.00 and hospital costs of Rp 5,000,000.00, as a form of responsibility and compensation to consumers who have experienced accidents. In the settlement of disputes of users of online transportation services that occur in go-car accident cases in Manado that occur by consumers are out of court (non-litigation) or familially in accordance with the results of the agreement of the parties. The conclusion of this study according to the authors of the implementation of compensation in the form of compensation or insurance to consumers of go-car online transportation service users as victims of accidents is unfair and not in accordance with the Regulation of the Minister of Finance No. 16 of 2017 on Large Compensation and Mandatory Contribution of Road Traffic Accident Fund, compensation for victims of road traffic accidents.